Are Tomato Farmers Willing to Adopt the Hydroponics Farming System in Oyo State, Nigeria? - Adepoju, Abimbola; Adekunle, Oluwaseun (Agricultura Scientia, 2023)
The rising demand for tomatoes and tomato-based foods in Nigeria owing to its numerous health benefits calls for a comprehensive and economically viable farming system to replace or complement traditional farming systems for tomato production. This study therefore assessed the level of awareness of tomato farmers and their readiness to adopt the hydroponics farming system. The sociodemographic determinants of their readiness to adopt hydroponic farming were also identified. Measures of central tendency and the logistic regression model were employed in the analysis of data. Knowledge of hydroponic farming was low among the farmers. Key positive determinants of awareness include distance to market, having governmentsupport and access to social media. More than three-fifths of the farmers were willing to adopt the hydroponics farming system. Such farmers had tertiary education, access to extension agents and relatively small farm sizes. High initial capital for adoption was the most critical limitation to the readiness of adoption of the system. Enhanced tomato output from this system may be a cause for its advocacy. Awareness and adoption of hydroponic farming can be increased if extension services are intensified. This will ensure food security and sustainable economic development.
Keywords: hydroponics farming system; willingness to adopt; tomato; awareness